American Civil Liberties Union of Northern California Honors Howard Watkins with Lola Hanzel Courageous Advocacy Award - Watkins, Howard::::::::: (1987)
Fred Korematsu talking with Christine Watkins Luncheon at Sheraton Palace Hotel in San Francisco